Preparation method and application of efficient antibacterial and anticorrosive titanium implant / MXene-based functional surface

By smoothing the titanium implant, alkalizing treatment and dense film preparation, and hybridizing the MXene nanosheets with metal oxides and depositing them on the surface of the titanium implant, a functionalized surface with photothermal synergistic antibacterial and anticorrosive properties was constructed, which solved the problem of insufficient antibacterial performance and corrosion of the titanium implant, and achieved excellent antibacterial and anticorrosive effects.

CN119587761AActive Publication Date: 2025-03-11NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH

Patent Information

Application Number
CN202411765402.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

Titanium implants lack inherent antibacterial properties, which easily leads to postoperative infection. In the corrosive environment in the body, the TiO2 passivation film is easily damaged, resulting in accelerated corrosion on the surface of the titanium implant, which in turn affects its long-lasting service and sustainable development.

Method used

The dense film was prepared by smoothing the titanium implant, alkalizing treatment, and impregnating it in a silane coupling agent or a biologically inspired binder solution, and the MXene-based multifunctional nanohybrid material obtained after hybridizing the two-dimensional MXene nanosheets with metal oxides was deposited to construct a titanium implant/MXene-based functionalized surface with photothermal synergistic antibacterial and anticorrosive properties.

Benefits of technology

The corrosion resistance of the dense film on the surface of the titanium implant is improved, and bacterial growth is effectively inhibited by the production of local thermal effects under near-infrared light, giving the titanium implant excellent antibacterial properties and significantly improving the anticorrosion performance of the titanium implant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119587761A_ABST
    Figure CN119587761A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an efficient antibacterial and anticorrosive titanium implant / MXene-based functional surface. The method comprises the following steps: 1, preparing an MXene-based multifunctional nano hybrid material; 2, pretreating the surface of the titanium implant; 3, preparing a compact film; and 4, functional surface preparation. According to the method, a nano hybrid material of the two-dimensional MXene nanosheet and the metal oxide is deposited on the surface of the titanium implant subjected to chemical pretreatment to form a functional surface with corrosion resistance, antibacterial performance and near-infrared light response performance, so that the corrosion resistance of a coating on the surface of the titanium implant is improved; the MXene-based multifunctional nano-hybrid material and the titanium implant / MXene-based functional surface have the advantages that the MXene-based multifunctional nano-hybrid material can be used for preparing the MXene-based functional surface, the growth of bacteria can be effectively inhibited by generating local heat effects under the irradiation of near-infrared light, excellent antibacterial performance can be given to titanium implantation, and the MXene-based multifunctional nano-hybrid material and the preparation method of the titanium implant / MXene-based functional surface have wide application prospects in functional application of biomedical coatings and titanium implants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomedical coatings, and specifically relates to a method for preparing a highly efficient antibacterial and anticorrosive titanium implant / MXene-based functionalized surface and its application. Background Art

[0002] Titanium implants are widely used in many fields including orthopedics (artificial joint replacement, fracture internal fixation), stomatology (dental implants), plastic surgery (skull repair), etc. due to their good mechanical properties, mechanical properties and biocompatibility. With their excellent performance in bearing high loads, avoiding biological rejection and long-term stability, they provide reliable guarantee for functional restoration and treatment support for patients.

[0003] However, titanium implants lack intrinsic antibacterial properties, and even comprehensive disinfection and aseptic operation during surgery cannot avoid postoperative infections caused by bacterial biofilm formation. In order to avoid infection-induced complications and secondary surgical consequences, titanium implants need to be endowed with good antibacterial properties. Secondly, titanium alloys are generally considered to have high biocompatibility and corrosion resistance because titanium can form a TiO2 passivation film after contact with oxygen, acting as a physical barrier between corrosive substances in the body and titanium metal. However, after titanium implants are implanted in the human body, due to the large amount of corrosive ions and corrosive microenvironments contained in the body fluid environment, once the TiO2 passivation film is damaged, the formation of corrosion potential and the effects of various chemical and biological factors in the body will accelerate the occurrence of corrosion. During bacterial infection, the acidic substances produced by bacterial metabolism in the biofilm will also lead to a local acidic environment of the titanium implant. These factors will accelerate the local corrosion of the surface of the titanium implant, which is manifested as typical pitting and mechanical factors-assisted crevice corrosion. The damage of the oxide layer will not only cause serious damage to the surface structure of the implant, reduce the mechanical properties, and cause problems such as implant fracture and loosening, resulting in implant failure; the alloy elements in the titanium alloy will dissolve and release Al, V and Ni ions into the surrounding tissues and body fluids, which will have toxic side effects on the human body and cause inflammatory reactions. Therefore, the inflammatory reactions and implant failures caused by postoperative infection, corrosion damage and release of toxic secondary ions in titanium implants seriously threaten the life safety of patients and become a bottleneck problem affecting the long-term service life and sustainable development of titanium implants.

[0004] The surface properties of titanium implants can be effectively improved by preparing nanostructured coatings and films on the surface of titanium and alloys through surface modification technology. Among them, MXene, as a new type of graphene oxide-like two-dimensional nanomaterial, has shown broad potential in the fields of regenerative medicine and tissue engineering due to its excellent photothermal properties, rich surface ends, high hydrophilicity, chemical stability, and antibacterial activity, and has become one of the most promising materials for functionalized applications of implant surfaces. Studies have shown that MXene has multiple antibacterial action modes, including the synergistic effects of chemical and physical factors: as a photothermal material, it can effectively kill bacteria by generating local heat through light; as a nanoknife, its sharp edge and its direct physical contact with the surface of the bacterial membrane will destroy the bacterial cell structure and cause the bacteria to release cytoplasm; as a reactive oxygen species (ROS) generator, it can generate different types of ROS, leading to bacterial death.

[0005] The patent application number 202410118173.7 discloses a ROS-responsive micro-nanostructure titanium implant nanocoating, which is obtained by self-assembly of a thioetherketone dopamine molecular coating on the surface of the micro-nanostructure implant and macrophage-targeted functionalized Nb2C MXene nanosheets. It solves the problem of periprosthetic bone dissolution faced by orthopedic prosthesis implants, and the preparation method is simple and the materials are readily available.

[0006] A MXene / metal nanoparticle multifunctional coating composite material is disclosed in the patent application number 202310247531.X. The prepared MXene-based multifunctional coating composite material does not destroy the surface structure of the substrate, retains the mechanical properties of the substrate, and has a strong bonding force between the substrate and the functional layer.

[0007] A method for preparing a MXene@cuttlefish juice melanin complex with photothermal synergistic antibacterial properties is disclosed in the patent with application number 202211043605.X. In the invention, cuttlefish juice melanin is evenly distributed or encapsulated in the composite formed on the surface or inside of MXene nanosheets. MXene has high photothermal properties and sharp edges that can effectively cut through the bacterial cell walls to achieve a bactericidal effect. In addition, using biomass cuttlefish juice melanin, which has a large stock, low price, and is environmentally friendly, as a template, the inherent agglomeration and stacking problems of MXene are improved, and the biocompatibility of the complex is enhanced; the MXene@cuttlefish juice melanin complex has excellent photothermal and mechanical antibacterial properties, and has broad application prospects in the fields of broad-spectrum antibacterial, tumor inhibition, and catalysis.

[0008] A MXene-ZnO nanohybrid material is disclosed in the patent with application number 202210356362.9. The MXene-ZnO nanohybrid material is synthesized by a low-temperature water bath, which has excellent synergistic antibacterial effect. It is further simply blended with polydimethylsiloxane, dispersed in solvents such as dichloromethane and ethyl acetate, and finally sprayed on substrates such as cotton cloth and fiber paper to obtain a hydrophobic antibacterial material with excellent antibacterial effect, rapid sterilization by photothermal synergistic effect, self-cleaning, and reusable.

[0009] It can be seen that the rich functional groups on the surface of MXenes also make it possible to give MXenes new properties or improve their own properties by hybridizing them with other materials, ultimately leading to enhanced antibacterial properties by providing synergistic effects, which makes MXene nanosheets have the potential to develop functionalized surfaces for titanium implants. However, current research focuses on optimizing the design by utilizing the excellent antibacterial properties of MXene nanomaterials, without fully considering the corrosion of titanium implants in complex body fluid environments.

[0010] Therefore, it is necessary to design a method for surface modification of titanium implants that takes into account both anti-corrosion and antibacterial applications. Summary of the invention

[0011] The technical problem to be solved by the present invention is to provide a method for preparing a highly efficient antibacterial and anticorrosive titanium implant / MXene-based functionalized surface in view of the deficiencies of the above-mentioned prior art. The method prepares a dense film by smoothing and alkalizing the titanium implant and immersing it in a silane coupling agent solution or a bio-inspired adhesive solution, and deposits a MXene-based multifunctional nano-hybrid material obtained by hybridizing two-dimensional MXene nanosheets with metal oxides to obtain a titanium implant / MXene-based functionalized surface, which not only improves the corrosion resistance of the dense film on the surface of the titanium implant, but also enables the titanium implant to effectively inhibit bacterial growth by generating a local thermal effect under near-infrared light irradiation, giving it excellent antibacterial properties.

[0012] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a highly efficient antibacterial and anticorrosive titanium implant / MXene-based functionalized surface, characterized in that the method comprises the following steps:

[0013] Step 1, preparation of MXene-based multifunctional nano-hybrid material: adding anhydrous ethanol to an aqueous solution of two-dimensional MXene and stirring at room temperature to obtain a MXene dispersion, then adding metal oxide nanomaterials to the MXene dispersion and stirring at room temperature to obtain a mixed solution, and then subjecting the mixed solution to a hydrothermal reaction and centrifugation to obtain a MXene-based multifunctional nano-hybrid material;

[0014] Step 2, surface pretreatment of the titanium implant: sequentially performing smoothing treatment and alkalization treatment on the titanium implant to obtain a surface pretreated titanium implant;

[0015] Step 3, preparation of a dense film on the surface of a titanium implant: immersing the surface pretreated titanium implant obtained in step 2 in a silane coupling agent solution or a bio-inspired adhesive solution to form a dense film with a three-dimensional network structure on the surface of the titanium implant, thereby obtaining a titanium implant with a dense film on the surface;

[0016] Step 4. Preparation of titanium implant / MXene-based functionalized surface: depositing the MXene-based multifunctional nano-hybrid material prepared in step 1 on the surface of the titanium implant having a dense thin film obtained in step 3 to obtain a titanium implant / MXene-based functionalized surface.

[0017] The present invention disperses two-dimensional MXene nanosheets and then hybridizes them with metal oxide nanomaterials so that the two are combined through covalent bonds, which not only improves the stability of the MXene nanosheets, but also significantly improves the antibacterial and corrosion resistance of the MXene-based multifunctional nano-hybrid materials by utilizing the synergistic effect provided by hybridization. The surface of the titanium implant is made smooth by smoothing treatment, which is convenient for subsequent alkalization treatment and preparation of dense films. The alkalization treatment introduces hydroxyl radicals into the surface of the titanium implant, which enhances the adhesion of the dense film. The surface pretreated titanium implant is immersed in a silane coupling agent solution or a bio-inspired adhesive solution to obtain a hydroxyl radical on the surface. Pretreating the surface of the titanium implant to prepare a dense thin film, that is, introducing a transition layer, improves the adhesion ability of the MXene-based multifunctional nano-hybrid material on the surface of the titanium implant, facilitates the subsequent deposition of the MXene-based multifunctional nano-hybrid material, and constructs a titanium implant / MXene-based functional surface with photothermal synergistic antibacterial and anti-corrosion properties. The MXene-based functionalized surface not only improves the corrosion resistance of the titanium implant surface coating, but also enables the titanium implant to effectively inhibit bacterial growth by generating a local thermal effect under near-infrared light irradiation, thereby giving it excellent antibacterial properties.

[0018] The above-mentioned method for preparing a highly efficient antibacterial and anticorrosive titanium implant / MXene-based functionalized surface is characterized in that the volume ratio of water and anhydrous ethanol in the MXene dispersion in step 1 is 1 to 4:1, and the anhydrous ethanol is added and stirred at room temperature for 0.5h to 3h. The mass ratio of metal oxide nanomaterial to MXene in the mixed solution is 1:1 to 4, and the metal oxide nanomaterial is added and stirred at room temperature for 2h to 5h. The hydrothermal reaction is carried out in a high-pressure reactor lined with polytetrafluoroethylene. The hydrothermal reaction and centrifugation process are: heating to 100°C and keeping warm for 4h to 8h, then cooling to room temperature, centrifuging the obtained product with a centrifuge at a speed of 3500rpm to 5000rpm, then pouring the supernatant, washing the precipitate with deionized water and anhydrous ethanol, and then centrifuging at a speed of 3500rpm to 5000rpm, and repeating the washing and centrifugation process 3 to 5 times to obtain a paste-like homogeneous black solution, namely, a MXene-based multifunctional nano-hybrid material. The present invention ensures uniform dispersion of MXene in the MXene dispersion by controlling the parameters of MXene dispersion, ensures covalent bonding of MXene nanosheets with metal oxide nanomaterials and integrity of the MXene sheet structure by controlling the parameters of the hydrothermal reaction, improves the dispersibility and stability of MXene nanosheets, and endows MXene-based multifunctional nano-hybrid materials with enhanced antibacterial and corrosion resistance through the synergistic effect provided by hybridization with metal oxides.

[0019] The above-mentioned method for preparing a highly efficient antibacterial and anticorrosive titanium implant / MXene-based functionalized surface is characterized in that the metal oxide nanomaterial in step 1 is iron oxide (Fe2O3), zinc oxide (ZnO), titanium dioxide (TiO)2, zirconium oxide (ZrO2) nanoparticles; the MXene is Ti3C2T x MXene, Mo2CT x MXene or Nb2CT x MXene. The present invention is applicable to different working conditions by controlling the specific composition of metal oxide nanomaterials and MXene.

[0020] The above-mentioned method for preparing a highly efficient antibacterial and anticorrosive titanium implant / MXene-based functionalized surface is characterized in that the smoothing process described in step 2 is: ultrasonically treat the titanium implant in a metal cleaning agent for 20min to 60min, then ultrasonically treat it in anhydrous ethanol for 20min to 60min, then rinse it with deionized water and dry it, then use 400# to 2000# sandpaper for step-by-step dry grinding, use 3000# sandpaper to wet grind under water until there are no obvious scratches and grooves on the surface and the surface color is grayish white, and finally use acetone, anhydrous ethanol and deionized water to ultrasonically clean it for 10min to 30min and dry it. The present invention makes the titanium implant smooth by controlling the parameters of the smoothing treatment, ensures that the alkali solution in the subsequent alkalization treatment process can fully and evenly contact the implant surface, and makes the stress and components of the pretreated titanium implant surface generated by the alkalization treatment evenly distributed.

[0021] The above-mentioned method for preparing a highly efficient antibacterial and anticorrosive titanium implant / MXene-based functionalized surface is characterized in that the alkalization treatment in step 2 is a plasma electrolytic oxidation alkalization treatment method, an electrochemical alkalization treatment method or an alkali solution immersion method; the process of the plasma electrolytic oxidation alkalization treatment method is: immersing the titanium implant after smoothing treatment in a stainless steel container having 10g / L to 20g / L NaAlO2 and 1.5g / L to 2g / L Na3PO4·12H2O solution, and then using a DC power supply to smooth The treated titanium implant is the anode, the electrolytic solution is the cathode, and the electrolysis is carried out for 5min to 10min under the conditions of voltage of 200V to 500V, frequency of 500Hz, and duty cycle of 5% to 20%, and then the implant is taken out, rinsed with deionized water and dried; the process of the electrochemical alkalization treatment method is: the titanium implant after the smooth treatment is placed in a NaOH electrolyte with 0.1-1mol / L, the titanium implant is used as the working electrode, the platinum electrode is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode to form a three-electrode system. The treatment is carried out for 10-30min under the condition of voltage of 1-10V, and then the implant is taken out, rinsed with deionized water and dried; the alkali solution immersion method includes the following steps: the titanium implant after the smooth treatment is placed in a reactor with a NaOH solution of 5mol / L to 10mol / L, and then hydrothermally treated at 100°C for 12h to 24h, and then taken out after cooling to room temperature, rinsed with deionized water and dried. The present invention increases the surface roughness of the titanium implant by adopting a plasma electrolytic oxidation alkalization treatment method, an electrochemical alkalization treatment method or an alkali solution immersion method, forms a dense oxide layer, increases hydrophilicity, and incorporates hydroxyl radicals (-OH) into the surface, so that a subsequent dense film can better adhere to the surface of the titanium implant.

[0022] The above-mentioned method for preparing a highly efficient antibacterial and anticorrosive titanium implant / MXene-based functionalized surface is characterized in that the process of immersing in a silane coupling agent solution in step three is: slowly stirring a solution consisting of 5% to 10% by mass of a silane coupling agent, 85% to 90% anhydrous ethanol and the remainder of deionized water for 1 hour for sufficient hydrolysis, and then soaking the surface pretreated titanium implant obtained in step two in the hydrolyzed solution for 1 hour to 2 hours, and then vacuum drying at 80°C to 100°C for 1 hour to 2 hours; the silane coupling agent is one of 3-aminopropyltriethoxysilane (KH550), γ-glycidyloxypropyltrimethoxysilane (KH560), γ-methacryloxypropyltrimethoxysilane (KH570) and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH792). The present invention forms a dense film, i.e., a transition layer, on the surface of a titanium implant by controlling the process of immersion in a silane coupling agent solution, thereby facilitating the subsequent deposition of a MXene-based multifunctional nano-hybrid material on the surface of the titanium implant.

[0023] The above-mentioned method for preparing a highly efficient antibacterial and anticorrosive titanium implant / MXene-based functionalized surface is characterized in that the process of immersing in a bio-inspired adhesive solution described in step three is: immersing the surface pretreated titanium implant in a container containing 50 mL of a bio-inspired adhesive solution, and then placing the container in a water bath shaker with a shaking radius of 3 cm and a rate of 30 rpm / min to 60 rpm / min, soaking for 12 h to 48 h at 25 ° C in a dark and shaking condition, then ultrasonically vibrating for 10 min to 30 min, and then placing in a vacuum drying oven at 40 ° C to 50 ° C to dry. The present invention forms a dense film, i.e., a transition layer, on the surface of the titanium implant by controlling the process of immersion in a bio-inspired adhesive solution, which facilitates the subsequent coating of MXene-based multifunctional nano-hybrid materials on the surface of the titanium implant.

[0024] The above-mentioned method for preparing a highly efficient antibacterial and anticorrosive titanium implant / MXene-based functionalized surface is characterized in that the bio-inspired adhesive solution is prepared by the following process: weigh 0.0788g of tris(hydroxymethyl)aminomethane hydrochloride and dissolve it in deionized water, then dilute it to 50mL in a volumetric flask to obtain 1mmol / L Tris buffer, then transfer the Tris buffer to a beaker, add 0.1000g of adhesive and mix well and continue stirring, and adjust the pH value to 8.5 with Tris buffer to obtain a bio-inspired adhesive solution; the adhesive is one or more of dopamine hydrochloride, chitosan quaternary ammonium salt or tannic acid solution. The bio-inspired adhesive in the present invention refers to a biomimetic wet bioadhesive inspired by mussels and barnacles, that is, an adhesive derived from natural resources, also called a bioadhesive, and an alkaline environment for spontaneous polymerization of the adhesive is provided by adjusting the pH value to 8.5.

[0025] The above-mentioned method for preparing a highly efficient antibacterial and anticorrosive titanium implant / MXene-based functionalized surface is characterized in that the deposition in step four is immersion deposition or drip deposition; the process of the immersion deposition is: diluting the MXene-based multifunctional nano-hybrid material prepared in step one with anhydrous ethanol to obtain a dilution with a concentration of 0.2 mg / mL to 2 mg / mL, and then immersing the titanium implant with a dense film on the surface in the dilution for 30 minutes, then taking it out and drying it in the air for 2 minutes, and repeating the immersion and drying three times, and then drying it at 37°C and 25kPa vacuum conditions for 4h to 8h; the process of the drip deposition is: diluting the MXene-based multifunctional nano-hybrid material prepared in step one with anhydrous ethanol to obtain a dilution with a concentration of 0.2 mg / mL to 2 mg / mL, and then the dilution is used in an amount of 0.5μL / mm 2 ~3μL / mm 2 The material is dripped onto the surface of a titanium implant having a dense film on the surface, and then dried at 37°C and 25 kPa vacuum conditions for 4 to 8 hours. The present invention prepares a uniform MXene-based multifunctional nano-hybrid material layer on the surface of the titanium implant by controlling the deposition process.

[0026] In addition, the present invention also provides an application of a highly effective antibacterial and anticorrosive titanium implant / MXene functionalized surface, characterized in that the preparation method of the MXene-based multifunctional nano-hybrid material and the titanium implant / MXene-based functionalized surface is applied to the surface modification of biomedical coatings and titanium implants. The present invention applies the MXene-based multifunctional nano-hybrid material and the preparation method of the titanium implant / MXene-based functionalized surface to the surface modification of biomedical coatings and titanium implants, solves the problems of inflammatory reactions and implant failure caused by postoperative infection, corrosion damage, and release of toxic secondary ions of titanium implants, and improves the antibacterial and corrosion behaviors of titanium implants.

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] 1. The present invention improves the adhesion ability of MXene-based multifunctional nano-hybrid materials on the surface of titanium implants by smoothing and alkalizing the titanium implants and immersing them in a silane coupling agent solution or a bio-inspired adhesive solution to form a dense film, i.e., introducing a transition layer. The present invention also constructs a functional surface with photothermal synergistic antibacterial and anti-corrosion properties by hybridizing two-dimensional MXene nanosheets with metal oxides to prepare MXene-based multifunctional nano-hybrid materials, thereby obtaining a titanium implant / MXene-based functionalized surface. The MXene-based multifunctional nano-hybrid materials not only improve the corrosion resistance of the titanium implant surface coating, but also effectively inhibit bacterial growth by generating a local thermal effect under near-infrared light irradiation, thereby giving titanium implants excellent antibacterial properties and showing broad application prospects in the functionalization of titanium implants.

[0029] 2. Electrochemical experiments on the titanium implant / MXene-based functionalized surface of the present invention show that it has excellent anti-corrosion properties and provides a corrosion resistance value Z f=0.01Hz This is two orders of magnitude higher than titanium implants with a dense film on the surface.

[0030] 3. The titanium implant / MXene functionalized surface of the present invention has excellent near-infrared photothermal properties. When a local thermal effect is generated after 10 minutes of irradiation with near-infrared light (1.5W), the functional surface temperature can reach nearly 72°C, which can significantly destroy the integrity of the bacterial membrane. However, the titanium metal surface is only 30°C. When the temperature is cooled to room temperature, the functional surface remains intact without cracking or peeling. The photothermal properties give the titanium implant / MXene functionalized surface excellent antibacterial ability, and the inhibition rate against Escherichia coli and Staphylococcus aureus is close to 100%.

[0031] 4. The titanium implant / MXene-based functionalized surface of the present invention has a simple, effective and low-cost preparation method and process, which provides a new option for the surface modification of titanium implants.

[0032] 5. The present invention applies the preparation method of titanium implant / MXene-based functionalized surface to the surface modification of titanium implants, and applies MXene-based multifunctional nano-hybrid materials to biomedical coatings, thereby solving the problems of inflammatory response and implant failure caused by postoperative infection, corrosion damage and release of toxic secondary ions of titanium implants, and improving the antibacterial and corrosion behaviors of titanium implants.

[0033] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a TEM image of the MXene used in step 1 of Example 1 of the present invention.

[0035] Figure 2 This is a TEM image of ZnO used in step 1 of Example 1 of the present invention.

[0036] Figure 3 This is a TEM image of the MXene / ZnO multifunctional nano-hybrid material obtained in step 1 of Example 1 of the present invention.

[0037] Figure 4 This is a Zeta potential diagram of the MXene and ZnO used in step 1 of Example 1 of the present invention and the MXene / ZnO multifunctional nano-hybrid material obtained in step 1.

[0038] Figure 5 The titanium implant used in step 2 of Example 1 of the present invention, the titanium implant with a dense thin film on the surface obtained in step 3, the Ti / MXene@ZnO functionalized surface obtained in step 4, and the surface optical morphology and water contact angle test graph of the Ti / MXene functionalized surface obtained by directly depositing MXene on the titanium implant.

[0039] Figure 6 The photothermal heating curves of the titanium implant used in step 2 of Example 1 of the present invention, the titanium implant with a dense thin film on the surface obtained in step 3, the Ti / MXene@ZnO functionalized surface obtained in step 4, and the Ti / MXene functionalized surface obtained by directly depositing MXene on the titanium implant under near-infrared light irradiation with a wavelength of 808 nm and a power of 1.5 W.

[0040] Figure 7 The titanium implant used in step 2 of Example 1 of the present invention, the titanium implant with a dense thin film on the surface obtained in step 3, the Ti / MXene@ZnO functionalized surface obtained in step 4, and the Ti / MXene functional surface obtained by directly depositing MXene on the titanium implant were tested for plate antibacterial results.

[0041] Figure 8 Bode diagram of electrochemical impedance spectroscopy of the titanium implant used in step 2 of Example 1 of the present invention, the titanium implant with a dense thin film on the surface obtained in step 3, the Ti / MXene@ZnO functionalized surface obtained in step 4, and the Ti / MXene functional surface obtained by directly depositing MXene on the titanium implant. DETAILED DESCRIPTION

[0042] Example 1

[0043] This embodiment includes the following steps:

[0044] Step 1: Preparation of MXene-based multifunctional nanohybrid materials: In 40 mL of 10 mg / mL two-dimensional monolayer Ti3C2T x 30 mL of anhydrous ethanol was added to the aqueous solution of MXene and stirred at room temperature for 3 h to obtain a MXene dispersion. Then, 0.4 g of zinc oxide quantum dots was added to the MXene dispersion and stirred at room temperature for 3 h to obtain a mixed solution. The mixed solution was then charged into a polytetrafluoroethylene-lined autoclave, heated to 100 ° C and hydrothermal for 4 h, cooled to room temperature, and the obtained product was centrifuged at a speed of 4000 rpm using a centrifuge. The supernatant was then poured out, and the precipitate was washed with deionized water and anhydrous ethanol and centrifuged at a speed of 4000 rpm. The washing and centrifugation process was repeated 4 times to obtain a paste-like homogeneous black solution, namely, a MXene-based multifunctional nanohybrid material.

[0045] Step 2, pretreatment of the titanium implant surface: a titanium implant with a diameter of 10 mm × height of 3 mm is ultrasonically treated in a metal cleaning agent for 30 minutes, then ultrasonically treated in anhydrous ethanol for 30 minutes, then rinsed with deionized water and dried, then dry-ground with 400#, 800#, 1000#, 1500#, and 2000# sandpapers in stages, wet-ground with 3000# sandpaper under water flow until there are no obvious scratches or grooves on the surface and the surface color is grayish white, finally ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water for 20 minutes and dried in turn to obtain a smooth titanium implant, the smooth titanium implant is placed in a reactor with a 10 mol / L NaOH solution, then hydrothermally treated at 100°C for 12 hours, then taken out after cooling to room temperature, rinsed with deionized water, and dried at 60°C to obtain a surface pretreated titanium implant;

[0046] Step 3, preparation of a dense film on the surface of a titanium implant: immerse the surface pretreated titanium implant obtained in step 2 in a container containing 50 mL of a bio-inspired adhesive solution, then place the container in a water bath shaker with a shaking radius of 3 cm and a speed of 50 rpm / min, soak for 24 hours under light-proof and shaking conditions at 25°C, then ultrasonically vibrate for 15 minutes, and then place in a vacuum drying oven at 45°C to dry, to obtain a titanium implant with a dense film on the surface; the bio-inspired adhesive solution is prepared by the following process: weigh 0.0788 g of trishydroxymethylaminomethane hydrochloride (Tris-HCl, chemical formula NH2C(CH2OH)3·HCl) and dissolve it in 30 mL of deionized water, then dilute to 50 mL in a volumetric flask to obtain 1 mmol / L Tris buffer, then transfer the Tris buffer to a beaker, add 0.1000 g of dopamine hydrochloride, mix well, and continue stirring, and adjust the pH value to 8.5 with Tris buffer to obtain a bio-inspired adhesive solution;

[0047] Step 4: Preparation of titanium implant / MXene-based functionalized surface: The MXene-based multifunctional nanohybrid material prepared in step 1 was diluted with anhydrous ethanol to obtain a dilution with a concentration of 1 mg / mL, and then the dilution was added at a concentration of 2 μL / mm 2 The titanium implant surface with a diameter of 10 mm and a dense film obtained in step 3 was dripped and then dried at 37°C and 25 kPa vacuum conditions for 6 h to obtain a Ti / MXene@ZnO functionalized surface.

[0048] It has been tested that when the MXene-based multifunctional nanohybrid material prepared in this embodiment is applied to the surface modification and biomedical coating of titanium implants, the constructed Ti / MXene@ZnO functionalized surface produces a local thermal effect under near-infrared light irradiation, has excellent photothermal antibacterial properties, and has significant anti-corrosion properties.

[0049] In step 1 of this embodiment, the metal oxide nanomaterials may also be iron oxide nanoparticles, titanium dioxide nanoparticles, and zirconium oxide nanoparticles.

[0050] In step 1 of this embodiment, MXene can also be Mo2CT x MXene or Nb2CT x MXene.

[0051] In step 2 of this embodiment, the smoothed titanium implant can also be placed in a reactor with a 5 mol / L NaOH solution and then hydrothermally treated at 100°C for 24 hours, or the smoothed titanium implant can be placed in a reactor with an 8 mol / L NaOH solution and then hydrothermally treated at 100°C for 18 hours.

[0052] In step three of this embodiment, the surface pretreated titanium implant obtained in step two can also be immersed in a container containing 50 mL of the bio-inspired adhesive solution, and then the container is placed in a water bath shaker with a shaking radius of 3 cm and a speed of 30 rpm / min, and immersed for 48 hours under the conditions of light-proof and shaking at 25°C, and then ultrasonically vibrated for 10 minutes, and then placed in a vacuum drying oven at 50°C for drying, or the surface pretreated titanium implant obtained in step two is immersed in a container containing 50 mL of the bio-inspired adhesive solution, and then the container is placed in a water bath shaker with a shaking radius of 3 cm and a speed of 60 rpm / min, and immersed for 12 hours under the conditions of light-proof and shaking at 25°C, and then ultrasonically vibrated for 30 minutes, and then placed in a vacuum drying oven at 40°C for drying.

[0053] In step three of this embodiment, the adhesive may also be one or more of dopamine hydrochloride, chitosan quaternary ammonium salt or tannic acid solution.

[0054] Figure 1 This is a transmission electron microscope (TEM) image of the MXene used in step 1 of this embodiment. Figure 2 This is the TEM image of ZnO used in step 1 of this embodiment. Figure 3 This is the TEM image of the MXene / ZnO multifunctional nanohybrid material obtained in step 1 of this embodiment. Figure 1 to Figure 3 It can be seen that in the MXene / ZnO multifunctional nanohybrid material, ZnO nanoparticles are evenly distributed on the surface of MXene nanosheets to form a typical sheet-dot structured nanocomposite material.

[0055] Figure 4 The Zeta potential diagram of the MXene and ZnO used in step 1 of this embodiment and the MXene / ZnO multifunctional nanohybrid material obtained in step 1 is shown in FIG. Figure 4 It can be seen that the MXene@ZnO multifunctional nanohybrid material prepared by hydrothermal reaction reduces the Zeta potential of MXene nanosheets and improves the stability of MXene nanosheets.

[0056] Figure 5 The titanium implant used in step 2, the titanium implant with a dense film on the surface obtained in step 3, the Ti / MXene@ZnO functionalized surface obtained in step 4, and the surface optical morphology and water contact angle test diagram of the Ti / MXene functionalized surface obtained by directly depositing MXene on the titanium implant, Figure 5 The titanium implant is denoted as Ti, the titanium implant with a dense film on the surface is denoted as Ti-PDA, and the Ti / MXene functionalized surface obtained by directly depositing MXene on the titanium implant is denoted as Ti / MXene. Figure 5 It can be seen that the surface of Ti-PDA forms a dense and uniform three-dimensional network structure, which improves the adhesion ability of MXene-based multifunctional nanohybrid materials on the surface of titanium implants with dense films. A crack-free Ti / MXene@ZnO functional surface is formed on the surface of titanium implants by the drip method. The hydrophilicity of the functional surface is increased, which is conducive to the adhesion and direct contact of bacterial cells, so that the MXene-based multifunctional nanohybrid materials show enhanced antibacterial effects.

[0057] Figure 6 The photothermal heating curves of the titanium implant used in step 2 of this embodiment, the titanium implant with a dense film on the surface obtained in step 3, the Ti / MXene@ZnO functionalized surface obtained in step 4, and the Ti / MXene functionalized surface obtained by directly depositing MXene on the titanium implant under near-infrared light irradiation with a wavelength of 808 nm and a power of 1.5 W, Figure 6The titanium implant was denoted as Ti, the titanium implant with a dense film on the surface was denoted as Ti-PDA, and the Ti / MXene functionalized surface obtained by directly depositing MXene on the titanium implant was denoted as Ti / MXene. The surfaces of Ti, Ti-PDA, Ti / MXene, and Ti / MXene@ZnO in a 24-well plate were irradiated using a near-infrared (NIR) emitter (808 nm, 1.5 W). The temperature of the centrifuge tube and the functional surface were monitored in real time using a thermal imager, and the temperature was recorded every 30 seconds for 10 minutes. Figure 6 It can be seen that under near-infrared light irradiation with a wavelength of 808nm and a power of 1.5W, the Ti / MXene and Ti / MXene@ZnO functional surfaces have excellent photothermal conversion efficiency compared with Ti-PDA and Ti, especially the Ti / MXene@ZnO functional surface. After 10 minutes of near-infrared light irradiation, the temperature can reach nearly 74°C, while the titanium implant surface is only 30°C.

[0058] The titanium implant used in step 2 of this embodiment, the titanium implant with a dense film on the surface obtained in step 3, the Ti / MXene@ZnO functionalized surface obtained in step 4, and the Ti / MXene functional surface obtained by directly depositing MXene on the titanium implant were subjected to a functional surface photothermal sterilization plate colony counting experiment, see Figure 7 , Figure 7 The titanium implant was denoted as Ti, the titanium implant with a dense film on the surface was denoted as Ti-PDA, and the Ti / MXene functionalized surface obtained by directly depositing MXene on the titanium implant was denoted as Ti / MXene. Before the plate colony counting experiment, the sample needed to be irradiated with UV light on both sides for 30 minutes. The sample was placed in a 24-well plate, and 1 mL of 1x10 6 CFU / ml of bacterial suspensions of Escherichia coli and Staphylococcus aureus were irradiated with a near-infrared (NIR) emitter (808nm, 1.5W) for 10 minutes on Ti, Ti-PDA, Ti / MXene and Ti / MXene@ZnO; after the photothermal treated samples were co-cultured in a 37°C constant temperature incubator for 6 hours, the bacterial suspension in the 24-well plate was diluted 100 times with PBS solution for a coating experiment, and then cultured in a 37°C constant temperature incubator overnight; the colonies in the plate were observed and counted (CFU) and the inhibition rate was calculated, the inhibition rate (%) = (control group CFU-experimental group CFU) / control group CFU, where the control group was a sample without near-infrared light irradiation and a sample with near-infrared light irradiation, marked as -NIR and +NIR, respectively, from Figure 7It can be seen that the Ti / MXene@ZnO functionalized surface has excellent photothermal sterilization effect due to its excellent photothermal conversion efficiency, which can significantly destroy the integrity of bacterial membranes, and the antibacterial rate against Escherichia coli (E.coil) and Staphylococcus aureus (S.aureus) is close to 100%.

[0059] Figure 8 In order to use the electrochemical workstation and three-electrode test system (the reference electrode is saturated AgCl / KCl, the auxiliary electrode is a platinum sheet with a length × width of 2 cm × 2 cm, and the working electrode is a working area of ​​0.785 cm 2 The Bode plot of the sample) obtained by electrochemical impedance spectroscopy EIS measurement, the horizontal axis is the logarithm of the frequency, the left ordinate is the corresponding impedance value result, and the right ordinate is the corresponding phase angle result. The selected electrolyte solution and test conditions are simulated body fluid SBF (37°C, 7.4, 200mL). The electrochemical impedance spectroscopy EIS measurement is carried out under non-polarized conditions. The frequency range of sinusoidal potential excitation is 100kHz~10mHz, the amplitude is 10mV, the titanium implant is denoted as Ti, the titanium implant with a dense film on the surface is denoted as Ti-PDA, and the Ti / MXene functionalized surface obtained by directly depositing MXene on the titanium implant is denoted as Ti / MXene. Figure 8 It can be seen that the Ti / MXene@ZnO functional surface has the best anti-corrosion performance, providing a corrosion resistance value Z f=0.01Hz Compared with Ti / MXene, the functional surface is improved by one order of magnitude and compared with Ti-PDA, it is improved by two orders of magnitude.

[0060] Example 2

[0061] This embodiment includes the following steps:

[0062] Step 1: Preparation of MXene-based multifunctional nanohybrid materials: In 40 mL of 10 mg / mL two-dimensional monolayer Ti3C2T x 40 mL of anhydrous ethanol was added to the aqueous solution of MXene and stirred at room temperature for 0.5 h to obtain a MXene dispersion. Then, 0.1 g of nano zinc oxide quantum dots was added to the MXene dispersion and stirred at room temperature for 5 h to obtain a mixed solution. The mixed solution was then charged into a polytetrafluoroethylene-lined autoclave, heated to 60 ° C and hydrothermally heated for 8 h, cooled to room temperature, and the obtained product was centrifuged at a speed of 3500 rpm using a centrifuge. The supernatant was then poured out, and the precipitate was washed with deionized water and anhydrous ethanol and centrifuged at a speed of 3500 rpm. The washing and centrifugation process was repeated 3 times to obtain a paste-like homogeneous black solution, namely, a MXene-based multifunctional nano-hybrid material.

[0063] Step 2: Surface pretreatment of titanium implants: Use a titanium sheet with a length × width × height of 10 mm × 10 mm × 3 mm as a titanium implant and ultrasonicate it in a metal cleaner for 20 minutes, then ultrasonicate it in anhydrous ethanol for 20 minutes, then rinse it with deionized water and dry it, then use 400#, 800#, 1000#, 1500#, 2000# sandpaper for step-by-step dry grinding, use 3000# sandpaper for wet grinding under water until there are no obvious scratches and grooves on the surface and the surface color is grayish white, finally use acetone, anhydrous ethanol and deionized water in turn. Ultrasonic cleaning with water for 30 minutes and drying to obtain a smooth titanium implant, immersing the smooth titanium implant in a stainless steel container with 15 g / L NaAlO2 and 1.6 g / L Na3PO4·12H2O solution, and then using a direct current power supply, with the smooth titanium implant as the anode and the electrolytic solution as the cathode, electrolyzing for 8 minutes under the conditions of voltage of 400 V, frequency of 500 Hz, and duty cycle of 20%, then taking out, rinsing with deionized water and drying at 60°C to obtain a surface pretreated titanium implant;

[0064] Step 3, preparation of a dense film on the surface of a titanium implant: slowly stirring a solution consisting of 5% by mass of a silane coupling agent, 90% anhydrous ethanol and the remainder of deionized water for 1 hour for sufficient hydrolysis, then soaking the surface pretreated titanium implant obtained in step 2 in the hydrolyzed solution for 1.5 hours, and then vacuum drying at 90°C for 1.5 hours to obtain a titanium implant with a dense film on the surface; the silane coupling agent is 3-aminopropyltriethoxysilane (KH550);

[0065] Step 4. Preparation of titanium implant / MXene-based functionalized surface: dilute the MXene-based multifunctional nano-hybrid material prepared in step 1 with anhydrous ethanol to obtain a dilution with a concentration of 1.0 mg / mL, and then immerse the titanium implant with a dense thin film on the surface in the dilution for 30 minutes, then take it out and dry it in the air for 2 minutes, and repeat the immersion and drying three times, and then dry it at 37°C and 25 kPa vacuum conditions for 6 hours to obtain a Ti / MXene@ZnO functionalized surface.

[0066] It has been tested that when the MXene-based multifunctional nanohybrid material prepared in this embodiment is applied to the surface modification and biomedical coating of titanium implants, the constructed Ti / MXene@ZnO functionalized surface produces a local thermal effect under near-infrared light irradiation, has excellent photothermal antibacterial properties, and has significant anti-corrosion properties.

[0067] In step 2 of this embodiment, the smoothed titanium implant can also be immersed in a stainless container having 10 g / L NaAlO2 and 2 g / L Na3PO4·12H2O solution, and then a DC power supply is used, with the smoothed titanium implant as the anode and the electrolytic solution as the cathode, and electrolysis is performed for 5 minutes at a voltage of 500 V, a frequency of 500 Hz, and a duty cycle of 5%, or the smoothed titanium implant can be immersed in a stainless container having 20 g / L NaAlO2 and 1.5 g / L Na3PO4·12H2O solution, and then a DC power supply is used, with the smoothed titanium implant as the anode and the electrolytic solution as the cathode, and electrolysis is performed for 10 minutes at a voltage of 200 V, a frequency of 500 Hz, and a duty cycle of 15%.

[0068] In step four of this embodiment, the MXene-based multifunctional nano-hybrid material prepared in step one can also be diluted with anhydrous ethanol to obtain a dilution with a concentration of 2 mg / mL, and then the titanium implant with a dense film on the surface is immersed in the dilution for 30 minutes, then taken out and dried in the air for 2 minutes, and the immersion and drying are repeated three times, and then dried at 37°C and 25 kPa vacuum conditions for 8 hours, or the MXene-based multifunctional nano-hybrid material prepared in step one is diluted with anhydrous ethanol to obtain a dilution with a concentration of 0.2 mg / mL, and then the titanium implant with a dense film on the surface is immersed in the dilution for 30 minutes, then taken out and dried in the air for 2 minutes, and the immersion and drying are repeated three times, and then dried at 37°C and 25 kPa vacuum conditions for 4 hours.

[0069] Example 3

[0070] This embodiment includes the following steps:

[0071] Step 1: Preparation of MXene-based multifunctional nanohybrid materials: In 50 mL of 10 mg / mL two-dimensional monolayer Ti3C2T x 12.5 mL of anhydrous ethanol was added to the aqueous solution of MXene and stirred at room temperature for 2 h to obtain a MXene dispersion. Then, 0.3 g of titanium dioxide nanoparticles was added to the MXene dispersion and stirred at room temperature for 2 h to obtain a mixed solution. The mixed solution was then charged into a polytetrafluoroethylene-lined autoclave, heated to 80 ° C and hydrothermal for 6 h, cooled to room temperature, and the obtained product was centrifuged at a speed of 5000 rpm using a centrifuge. The supernatant was then poured out, and the precipitate was washed with deionized water and anhydrous ethanol and centrifuged at a speed of 5000 rpm. The washing and centrifugation process was repeated 5 times to obtain a paste-like homogeneous black solution, namely, a MXene-based nanohybrid material.

[0072] Step 2, surface pretreatment of the titanium implant: a titanium sheet with a length × width × height of 10 mm × 10 mm × 3 mm is used as a titanium implant and ultrasonically treated in a metal cleaner for 60 minutes, then ultrasonically treated in anhydrous ethanol for 60 minutes, then rinsed with deionized water and dried, then dry-ground with 400#, 800#, 1000#, 1500#, and 2000# sandpapers in stages, wet-ground with 3000# sandpaper under water flow until there are no obvious scratches or grooves on the surface and the surface color is grayish white, finally ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water for 10 minutes in turn and dried to obtain a smoothed titanium implant, and the smoothed titanium implant is placed in an electrolyte with 0.1 mol / L NaOH, the titanium implant is used as a working electrode, the platinum electrode is used as a counter electrode, and the saturated calomel electrode is used as a reference electrode to form a three-electrode system. The surface of the titanium implant was treated at a voltage of 10 V for 30 min, and then taken out, rinsed with deionized water and dried to obtain a surface pretreated titanium implant;

[0073] Step 3, preparation of a dense film on the surface of a titanium implant: slowly stir a solution consisting of 10% by mass of a silane coupling agent, 85% of anhydrous ethanol and the remainder of deionized water for 1 hour to fully hydrolyze, then immerse the surface pretreated titanium implant obtained in step 2 in the solution for 1 hour, and then vacuum dry it at 100°C for 1 hour to obtain a titanium implant with a dense film on the surface; the silane coupling agent is γ-glycidyloxypropyltrimethoxysilane (KH560);

[0074] Step 4: Preparation of titanium implant / MXene-based functionalized surface: The MXene-based nanohybrid material prepared in step 1 was diluted with anhydrous ethanol to obtain a dilution with a concentration of 2 mg / mL, and then the dilution was added at a dosage of 0.5 μL / mm 2 The titanium implant surface with a dense film obtained in step three was dripped and then dried at 37°C and 25 kPa vacuum conditions for 4 hours to obtain a Ti / MXene@TiO2 functionalized surface.

[0075] It has been tested that when the MXene-based multifunctional nanohybrid material prepared in this embodiment is applied to the surface modification and biomedical coating of titanium implants, the constructed Ti / MXene@TiO2 functionalized surface produces a local thermal effect under near-infrared light irradiation, has excellent photothermal antibacterial properties, and has significant anti-corrosion properties.

[0076] In step 2 of this embodiment, the smoothed titanium implant can also be placed in a 1 mol / L NaOH electrolyte, with the titanium implant as the working electrode, the platinum electrode as the counter electrode, and the saturated calomel electrode as the reference electrode to form a three-electrode system, and treated at a voltage of 1 V for 10 min.

[0077] In step three of this embodiment, a solution consisting of 8% by mass of a silane coupling agent, 86% of anhydrous ethanol and the remainder of deionized water can be slowly stirred for 1 hour for sufficient hydrolysis, and then the surface pretreated titanium implant obtained in step two is immersed in it for 2 hours, and then vacuum dried at 80°C for 2 hours to obtain a titanium implant with a dense film on the surface; the silane coupling agent can also be one of 3-aminopropyltriethoxysilane (KH550), γ-methacryloxypropyltrimethoxysilane (KH570) and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH792).

[0078] In step 4 of this embodiment, the MXene-based nanohybrid material prepared in step 1 can be diluted with anhydrous ethanol to obtain a dilution with a concentration of 0.2 mg / mL, and then the dilution is added at a dosage of 3 μL / mm 2 The titanium implant surface having a dense film obtained in step 3 is dripped and then dried at 37° C. and 25 kPa vacuum conditions for 8 h.

[0079] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a highly efficient antibacterial and anticorrosive titanium implant / MXene-based functionalized surface, characterized in that: The method comprises the following steps: Step 1, preparation of MXene-based multifunctional nano-hybrid material: adding anhydrous ethanol to an aqueous solution of two-dimensional MXene and stirring at room temperature to obtain a MXene dispersion, then adding metal oxide nanomaterials to the MXene dispersion and stirring at room temperature to obtain a mixed solution, and then subjecting the mixed solution to a hydrothermal reaction and centrifugation to obtain a MXene-based multifunctional nano-hybrid material; Step 2, surface pretreatment of the titanium implant: sequentially performing smoothing treatment and alkalization treatment on the titanium implant to obtain a surface pretreated titanium implant; Step 3, preparation of a dense film on the surface of a titanium implant: immersing the surface pretreated titanium implant obtained in step 2 in a silane coupling agent solution or a bio-inspired adhesive solution to form a dense film with a three-dimensional network structure on the surface of the titanium implant, thereby obtaining a titanium implant with a dense film on the surface; Step 4. Preparation of titanium implant / MXene-based functionalized surface: depositing the MXene-based multifunctional nano-hybrid material prepared in step 1 on the surface of the titanium implant having a dense thin film obtained in step 3 to obtain a titanium implant / MXene-based functionalized surface.

2. The method for preparing a highly efficient antibacterial and anticorrosive titanium implant / MXene-based functionalized surface according to claim 1, characterized in that: In step 1, the volume ratio of water to anhydrous ethanol in the MXene dispersion is 1 to 4:1, and the anhydrous ethanol is added and stirred at room temperature for 0.5 h to 3 h. The mass ratio of metal oxide nanomaterial to MXene in the mixed solution is 1:1 to 4, and the metal oxide nanomaterial is added and stirred at room temperature for 2 h to 5 h. The hydrothermal reaction is carried out in a high-pressure reactor lined with polytetrafluoroethylene. The hydrothermal reaction and centrifugation process are as follows: heating to 60 to 100 ° C and keeping warm for 4 h to 8 h, and then cooling to room temperature. The obtained product is centrifuged at a speed of 3500 rpm to 5000 rpm by a centrifuge, and then the supernatant is poured out, and the precipitate is washed with deionized water and anhydrous ethanol and then centrifuged at a speed of 3500 rpm to 5000 rpm. The washing and centrifugation process is repeated 3 to 5 times to obtain a paste-like homogeneous black solution, namely, a MXene-based multifunctional nano-hybrid material.

3. The method for preparing a highly efficient antibacterial and anticorrosive titanium implant / MXene-based functionalized surface according to claim 1, characterized in that: The metal oxide nanomaterials in step 1 are iron oxide (Fe2O3), zinc oxide (ZnO), titanium dioxide (TiO)2, zirconium oxide (ZrO2) nanoparticles; the MXene is Ti3C2T x MXene, Mo2CT x MXene or Nb2CT x MXene.

4. The method for preparing a highly efficient antibacterial and anticorrosive titanium implant / MXene-based functionalized surface according to claim 1, characterized in that: The smoothing process described in step 2 is: ultrasonically treat the titanium implant in a metal cleaning agent for 20 minutes to 60 minutes, then ultrasonically treat it in anhydrous ethanol for 20 minutes to 60 minutes, then rinse it with deionized water and dry it, then use 400# to 2000# sandpaper for step-by-step dry grinding, use 3000# sandpaper for wet grinding under water until there are no obvious scratches and grooves on the surface and the surface color is grayish white, finally use acetone, anhydrous ethanol and deionized water for ultrasonic cleaning for 10 minutes to 30 minutes and dry it.

5. The method for preparing a highly efficient antibacterial and anticorrosive titanium implant / MXene-based functionalized surface according to claim 1, characterized in that: The alkalization treatment in step 2 is a plasma electrolytic oxidation alkalization treatment method, an electrochemical alkalization treatment method or an alkali solution immersion method; the process of the plasma electrolytic oxidation alkalization treatment method is: immersing the titanium implant after smoothing treatment in a stainless steel container having 10g / L~20g / L NaAlO2 and 1.5g / L~2g / L Na3PO4·12H2O solution, and then using a DC power supply, with the titanium implant after smoothing treatment as the anode and the electrolytic solution as the cathode, electrolyzing for 5min~10min under the conditions of voltage of 200V~500V, frequency of 500Hz, and duty cycle of 5%~20%, and then taking it out, rinsing it with deionized water and drying it; the process of the electrochemical alkalization treatment method is: placing the titanium implant after smoothing treatment in a NaOH electrolyte having 0.1~1mol / L, using the titanium implant as the working electrode, the platinum electrode as the counter electrode, and the saturated calomel electrode as the reference electrode to form a three-electrode system. The titanium implant is treated at a voltage of 1-10V for 10 to 30 minutes, then taken out, rinsed with deionized water and dried; the alkaline solution immersion method comprises the following steps: placing the titanium implant after smoothing in a reactor with a 5mol / L to 10mol / L NaOH solution, then hydrothermally treated at 100°C for 12h to 24h, then taken out after cooling to room temperature, rinsed with deionized water and dried.

6. The method for preparing a highly efficient antibacterial and anticorrosive titanium implant / MXene-based functionalized surface according to claim 1, characterized in that: The process of impregnation in the silane coupling agent solution described in step 3 is: slowly stirring a solution consisting of 5% to 10% by mass of a silane coupling agent, 85% to 90% anhydrous ethanol and the remainder of deionized water for 1 hour to fully hydrolyze, then soaking the surface pretreated titanium implant obtained in step 2 in the hydrolyzed solution for 1 hour to 2 hours, and then vacuum drying at 80° C. to 100° C. for 1 hour to 2 hours; the silane coupling agent is one of 3-aminopropyltriethoxysilane (KH550), γ-glycidyloxypropyltrimethoxysilane (KH560), γ-methacryloxypropyltrimethoxysilane (KH570) and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH792).

7. The method for preparing a highly efficient antibacterial and anticorrosive titanium implant / MXene-based functionalized surface according to claim 1, characterized in that: The process of immersion in the bio-inspired adhesive solution described in step three is: immerse the surface pretreated titanium implant in a container containing 50 mL of the bio-inspired adhesive solution, and then place the container in a water bath shaker with a shaking radius of 3 cm and a speed of 30 rpm / min to 60 rpm / min, soak for 12 h to 48 h at 25 ° C in a dark and shaking condition, then ultrasonically vibrate for 10 min to 30 min, and then place in a vacuum drying oven at 40 ° C to 50 ° C to dry.

8. The method for preparing a highly efficient antibacterial and anticorrosive titanium implant / MXene-based functionalized surface according to claim 1, characterized in that: The bio-inspired adhesive solution is prepared by the following process: 0.0788 g of tris(hydroxymethyl)aminomethane hydrochloride) is weighed and dissolved in deionized water, and then the volume is adjusted to 50 mL in a volumetric flask to obtain a 1 mmol / L Tris buffer, and then the Tris buffer is transferred to a beaker, 0.1000 g of an adhesive is added, mixed evenly, and then stirred continuously, and the pH value is adjusted to 8.5 with the Tris buffer to obtain a bio-inspired adhesive solution; the adhesive is one or more of dopamine hydrochloride, chitosan quaternary ammonium salt or tannic acid solution.

9. The method for preparing a highly efficient antibacterial and anticorrosive titanium implant / MXene-based functionalized surface according to claim 1, characterized in that: The deposition in step 4 is immersion deposition or drip deposition; the process of immersion deposition is: diluting the MXene-based multifunctional nano-hybrid material prepared in step 1 with anhydrous ethanol to obtain a dilution with a concentration of 0.2 mg / mL to 2 mg / mL, and then immersing the titanium implant with a dense film on the surface in the dilution for 30 minutes, then taking it out and drying it in the air for 2 minutes, and repeating the immersion and drying three times, and then drying it at 37°C and 25kPa vacuum conditions for 4h to 8h; the process of drip deposition is: diluting the MXene-based multifunctional nano-hybrid material prepared in step 1 with anhydrous ethanol to obtain a dilution with a concentration of 0.2 mg / mL to 2 mg / mL, and then diluting the dilution at a dosage of 0.5μL / mm 2 ~3μL / mm 2 The solution is dripped onto the surface of a titanium implant having a dense film, and then dried at 37°C and 25kPa vacuum conditions for 4 to 8 hours.

10. An application of a highly effective antibacterial and anticorrosive titanium implant / MXene-based functionalized surface as claimed in any one of claims 1 to 9, characterized in that: The preparation methods of the MXene-based multifunctional nano-hybrid materials and titanium implant / MXene-based functionalized surfaces are applied to surface modification of biomedical coatings and titanium implants.

Citation Information

Patent Citations

  • An MXene-zinc oxide nanocomposite material, its preparation method, and a recyclable hydrophobic antibacterial material obtained therefrom.

    CN114747593B

  • A MXene@cuttlefish juice melanin composite with photothermal synergistic antibacterial properties and its preparation method and application

    CN115531537B

  • Preparation method of MXene / metal nanoparticle multifunctional coating composite material

    CN116446177B

  • ROS response micro-nano structure titanium implant nano coating as well as preparation method and application thereof

    CN117919504A

  • Porous titanium-based implant with photo-thermal surface as well as preparation method and application of porous titanium-based implant

    CN120586149A

Cited By

  • Porous titanium-based implant with photo-thermal surface as well as preparation method and application of porous titanium-based implant

    CN120586149A

  • Near-infrared light response thermal-electric coupling titanium-based implant as well as preparation method and application of near-infrared light response thermal-electric coupling titanium-based implant

    CN122075783A

  • Heterogeneous high-entropy sandwich gradient coating as well as preparation method and application thereof

    CN122147308A